Direitos humanos e diversidade cultural: letramento digital e a aprendizagem histórica por meio do remix no ensino médio - Araújo, Alessandro Oliveira de Souza (2021)
The aim of this paper is to reflect on the importance of human rights education with a focus on cultural diversity. This theme has been historically neglected, even though there is ample legislation in Brazil that is the result of the country's signatory to the pacts that organize human rights. Another face of this problem is found in the methodology used historically in classrooms. Education must be aligned with the skills and knowledge of our students. Digital literacies are a methodology capable of combining these skills with a set of new skills that can be acquired. The remix, one of those forms of digital literacy, can function as a tool in historical learning about the formation of human rights. In order to produce a history teaching focused on the student and producer of subjects of law, a fundamental principle of human rights education, we will use in this work, the remix as a didactic proposal. For the use of the remix it is necessary to use a pre-existing artifact and in our case, we selected the audiovisual narratives (films) in the classroom as the media for the production of historical syntheses in the format of the remix. The films are audiovisual historical documents, which offer versions of the past and can be articulated in the classroom, based on a specific problem set up by the teacher. In our case, the theme of the formation of human rights and specifically the importance and respect for cultural diversity. In this work, field research (made with Google Forms) and experiences with the remix technique carried out in the classroom are presented and at the end we present an elective discipline proposal as a product aimed at learning human rights through the learning and use of remix.